2023
DOI: 10.1021/acs.accounts.3c00519
|View full text |Cite
|
Sign up to set email alerts
|

Dispersion Interactions in Asymmetric Induction for Constructing Vicinal Stereogenic Centers

Bo Li,
Hui Xu,
Yanfeng Dang

Abstract: Metrics & MoreArticle Recommendations * sı Supporting Information CONSPECTUS: Vicinal stereogenic centers are prevalent structural motifs of primary functional relevance in natural products and bioactive molecules. The quest for the rapid and controllable construction of vicinal stereogenic centers stands as a frontier endeavor in asymmetric organic synthesis. Over the past decade, stereodivergent synthesis has been intensely researched within the realm of bimetallic catalysis, aiming at establishing novel tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Notably, when London dispersion interactions are omitted from the calculations, the calculations fail to reproduce the observed enantioselectivity (Figure a). This underscores the significance of London dispersion interactions in enantioface discrimination . An independent gradient model based on Hirshfeld partition analysis (IGMH) reveals the presence of London dispersion interactions between the Cy and Ad in the TS-ax-S-cyclohexyl .…”
Section: Resultsmentioning
confidence: 99%
“…Notably, when London dispersion interactions are omitted from the calculations, the calculations fail to reproduce the observed enantioselectivity (Figure a). This underscores the significance of London dispersion interactions in enantioface discrimination . An independent gradient model based on Hirshfeld partition analysis (IGMH) reveals the presence of London dispersion interactions between the Cy and Ad in the TS-ax-S-cyclohexyl .…”
Section: Resultsmentioning
confidence: 99%
“…Our computations unambiguously predicted the formation of branched/branched products with the correct stereochemistry. A more detailed examination allowed us to identify steric hindrance as a prominent contributor to the observed selectivity. , …”
Section: Resultsmentioning
confidence: 99%
“…Intriguingly, we found that the flexible alkyl group adaptively avoids potential steric conflicts with the ligand, allowing for a congested linear-branched transition state. Moreover, the alkyl group allows extensive dispersion attraction within the inner pocket of the sizable chiral ligand. Collectively, these analyses reveal a substrate-dependent interplay between dispersion and steric effects that dictate regio- and stereoselectivities in the current inner-sphere bond-formation mechanism.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation